Component and shaking table tests for full-scale multiple friction pendulum system. - Tsai, C.S.
The use of base isolation in developed countries including the U.S. and Japan has already been recognized as a very effective method for upgrading the seismic resistance of structures. In this study, an advanced base-isolation system called the multiple friction pendulum system (MFPS) is investigated to understand its performance on seismic mitigation through full-scale component and shaking table tests. The component tests of the advanced Teflon composite coated on the sliding surface show that the friction coefficient of the lubricant material is a function of the sliding velocity in the range of 0.03?0.12. The experimental results also indicate that there were no signs of degradation of the sliding interface observed after 2000 cycles of sliding displacements. A full-scale MFPS isolator under a vertically compressive load of 8830 KN (900 tf) and horizontally cyclic displacements was tested in order to assess the feasibility of the MFPS isolator for its practical use. After 248 cycles of horizontal displacement reversals, the behaviour of the base isolator was almost identical to its behaviour during the first few cycles. The experimental results of the shaking table tests of a full-scale steel structure isolated with MFPS isolators show that the MFPS device can isolate seismic transmitted energy effectively under soft-soil-deposit site earthquakes with long predominant periods as well as strong ground motions with short predominant periods. These test results demonstrate that the MFPS isolator possesses excellent durability and outstanding earthquake-proof capability. Furthermore, the numerical results show that the mathematical model proposed in this study can well predict the seismic responses of a structure isolated with MFPS isolators.
Keywords: Base isolation; Friction pendulum; Shaking table tests; Component tests